Truth be told - Ryan, Hank Phillippi (Ryan, Hank Phillippi. Jane Ryland novel., 2014)
A middle-class family's evicted from their suburban home. In digging up the facts on this story and on other foreclosures, reporter Jane Ryland soon learns the truth behind a big-bucks scheme and the surprising players who'll stop at nothing, including murder, to keep their goal a secret.